Short Communication: The flowering process of Prunus cerasoides Buch.-Ham. Ex D.Don in Bali Botanic Garden - GEBBY AGNESSYA ESA OKTAVIA; RAJIF IRYADI; TRI WARSENO; HERY PURNOBASUKI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oktavia GAE, Iryadi R, Warseno T, Purnobasuki H. 2023. Short Communication: The flowering process of Prunus cerasoides Buch.-Ham. Ex D.Don in Bali Botanic Garden. Biodiversitas 24: 1186-1191. Prunus cerasoides Buch.-Ham. Ex D.Don is a native plant of the Indian-Indochinese floristic zone and one of the Eka Karya Bali Botanical Gardens' collection plants (EKBBG). Weather factors have an impact on the length of blossoming. Moreover, the microclimate variations study is a fascinating subject. A plant's adaptation is influenced by changes in the environment regularly. This research goal was to figure out how P. cerasoides flowers in EKBBG and how that relates to environmental parameters. The flowering time of four P. cerasoides trees from the EKBBG collection was observed. The weather from satellite data of the EKBBG Registration Unit provided environmental data in the form of air temperature, humidity, air pressure, and rainfall. The IBM SPSS Statistics 23 software was used to analyze the data. The results revealed that P. cerasoides in EKBBG flower twice a year, with the development stage of flower buds, blooming, and then the fall phase of the floral ornaments. Due to the blossoms falling, the fruit did not mature. Moreover, the number of blooms that develop is unaffected by temperature or UV index.